Application Of Value Engineering in Port Wharf Development in Gorontalo - Sofiyudin, Mahdi; Kurniawan, Prima; Suwela, Suwela; K, Aryati Indah (Ridwan Institute, 2025)
In an archipelagic and developing country like Indonesia, population growth and mobility continue to increase, necessitating extensive infrastructure development. However, significant infrastructure gaps persist, requiring inclusive and sustainable development strategies to ensure equitable benefits across society. This research aims to optimize infrastructure development budgets through value engineering (VE) methodology applied to the Gorontalo Port development project. The study employs a systematic approach using five VE phases: information gathering, creativity, analysis, development, and recommendations, analyzing cost optimization potential compared to Basic Engineering Design (BED) specifications. Data collection involved secondary sources, including Cost Budget Plans (RAB) and Basic Engineering Design drawings, with analysis focusing on pier building optimization and structural repair work optimization. The value engineering analysis produced significant cost optimization potential of IDR 86.83 billion compared to the original BED price of IDR 144.46 billion, resulting in savings of IDR 57.83 billion. The initial cost breakdown totaled IDR 144,466,589,384, which, after VE efficiency efforts, became IDR 86,831,436,530, achieving cost savings of IDR 57,615,152,854 or a 39.19% reduction. The analysis incorporated a 1.6% inflation adjustment for 2025, bringing the total project cost to IDR 89,236,739,514.48. Key value engineering applications included pier length optimization from 150 m to 100 m based on ship visit data analysis, alternative corrosion protection methods using FRP instead of HDPE, and structural repair optimization through alternative supplier selection. This research demonstrates that value engineering methodology effectively reduces construction costs while maintaining quality, specifications, and performance requirements, providing a systematic approach for infrastructure budget optimization in developing countries.